2016
DOI: 10.1039/c6ta03178a
|View full text |Cite
|
Sign up to set email alerts
|

Light-assisted rapid preparation of a Ni/g-C3N4 magnetic composite for robust photocatalytic H2 evolution from water

Abstract: Ni formed by photo-reduction of Ni(ii) within 30 min and the ratio of Ni/g-C3N4 can be adjusted conveniently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(133 citation statements)
references
References 34 publications
3
125
0
Order By: Relevance
“…Further examination reveals that the diffraction intensity of g‐C 3 N 4 gradually decreases with the increment of NiS 2 content. In principle, it should be the marked inhibition effect of NiS 2 QDs on the two‐dimensional structure that induces this diffraction reduction . Moreover, hydrothermal treatment in the presence of NH 3⋅ H 2 O could induce more defect on the surface g‐C 3 N 4 , which also contributes to the reduction of the peak intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Further examination reveals that the diffraction intensity of g‐C 3 N 4 gradually decreases with the increment of NiS 2 content. In principle, it should be the marked inhibition effect of NiS 2 QDs on the two‐dimensional structure that induces this diffraction reduction . Moreover, hydrothermal treatment in the presence of NH 3⋅ H 2 O could induce more defect on the surface g‐C 3 N 4 , which also contributes to the reduction of the peak intensity.…”
Section: Resultsmentioning
confidence: 99%
“…[207] For example, Kong et al [208] reported Ni/gC 3 N 4 with enhanced photocatalytic H 2 generation performance. [207] For example, Kong et al [208] reported Ni/gC 3 N 4 with enhanced photocatalytic H 2 generation performance.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Bimetallic cocatalysts such as PtCo, [205] PdAu, [239] PtOAu [240] have exhibited higher H 2 photocatalytic activity than single noble metals. So far, numerous nonnoble metal cocatalysts have proven efficient in enhancing the photo catalytic H 2 generation activity of gC 3 N 4 , including FeO x , [228] MoS 2 , [229,[241][242][243][244] WS 2 , [245] NiS, [246][247][248] Ni 12 P 5 , [249] carbon nanotube (CNT), [232] carbon black, [233] carbon nanofiber, [222] Co(OH) 2 , [250] Ni(OH) 2 , [251,252] Cu(OH) 2 , [253] Ni(dmgH) 2, [254] and Ni [208,255,256] (Table 3). So far, numerous nonnoble metal cocatalysts have proven efficient in enhancing the photo catalytic H 2 generation activity of gC 3 N 4 , including FeO x , [228] MoS 2 , [229,[241][242][243][244] WS 2 , [245] NiS, [246][247][248] Ni 12 P 5 , [249] carbon nanotube (CNT), [232] carbon black, [233] carbon nanofiber, [222] Co(OH) 2 , [250] Ni(OH) 2 , [251,…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…[6] In this regard, nickel-based co-catalysts are extremely important and well-studied systems. In addition, Ni, [10] NiS, [11] Ni-NiO, [12] and Ni(OH) 2 [13] systems with semiconductors have also been reported with good to moderate activity.N ickel phosphide (Ni 2 P), aw ell-known catalyst for the electrochemical proton reduction, [14] has not been explored much as ac o-catalyst in combination with as emiconductor for the photocatalytic HER. In addition, Ni, [10] NiS, [11] Ni-NiO, [12] and Ni(OH) 2 [13] systems with semiconductors have also been reported with good to moderate activity.N ickel phosphide (Ni 2 P), aw ell-known catalyst for the electrochemical proton reduction, [14] has not been explored much as ac o-catalyst in combination with as emiconductor for the photocatalytic HER.…”
mentioning
confidence: 99%